Pengaruh Travel Motivation dan Perceived Value Terhadap Minat Berkunjung Kembali di Desa Wisata Lebakmuncang Ciwidey - Putri, Pratiwi Pribadi; Edison, Emron (Sekolah Tinggi Ilmu Ekonomi Pariwisata Yapari (STIEPAR YAPARI) Bandung, 2024)
This research aims to determine the influence of travel motivation and perceived value on interest in visiting Lebakmuncang Ciwidey Tourism Village. This research method uses quantitative methods with descriptive analysis and verifiative analysis. The variables used are travel motivation, perceived value and interest in visiting again. The sample used amounted to 100 respondents, namely tourists who had visited Lebakmuncang Ciwidey Tourism Village. The results of the instrument test showed that all statements were declared valid because the value was above 0.300 and declared reliable because the value was above 0.700. From descriptive research, it is known that travel motivation, perceived value and interest in visiting again as a whole are included in the